PENERAPAN ALAT PERAGA PERNAFASAN PEMBELAJARAN IPAS PADA SISWA KELAS V SDN WATUWUNGKUK DRINGU PROBOLINGGO - Abdullah, Cowima Fanza Maulida; Prayogo, Muhammad Suwignyo; Musharrofah, Nadiatul; Fadila, Badriatul (Abtadi : Jurnal Pendidikan Dasar, 2024)
ABSTRACT The Independent Curriculum requires students to be more active indeveloping their knowledge during learning activities. For this reason, teaching aids areneeded to enrich the learning experience of students. This research aims to find out how toapply breathing aids to the human anatomy model for science learning in grade 5 students atSDN Watuwungkuk Dringu Probolinggo. The research method used is a qualitative methodwith data obtained through observation, interviews and documents. The results of theresearch explain that the learning process in the school which uses human respiratoryanatomy model teaching aids is effective in increasing students' understanding becausestudents are able to visualize abstract concepts in the learning material. Researchers wouldlike to encourage future researchers to develop other teaching aids that are more interactive,especially with advances in technology and digitalization, so that they can be implementedin learning.